PENGARUH GAYA KEPEMIMPINAN DAN KOMPENSASI TERHADAP KINERJA KARYAWAN: Studi Pada TOYOTA AUTO 2000 Hasanudin Kediri - Sri Astutik, Wahyuni; Setiyo Budi, Nunung (JUMBA (Jurnal Manajemen, Bisnis, dan Akuntansi), 2022)
This study aims to determine the effect of leadership style and compensation on employee performance (study at Toyota Auto 2000 Hasanudin Kediri). The research variables used are Leadership Style (X1), Compensation (X2) and Employee Performance (Y). The data collection techniques are interviews, observations, literature studies and questionnaires. The analysis used in this study is validity test, reliability test, classical assumption test, multiple linear regression test, t test and F test using SPSS software program version 22. Based on tests conducted with multiple linear regression analysis, it is proven that the variables of Leadership Style (X1), Compensation (X2), partially or simultaneously have a significant effect on Employee Performance (Y) at Toyota Auto 2000 Hasanudin, and the variable that has the most dominant influence on employee performance is the leadership style variable.